2022
DOI: 10.1097/sap.0000000000003182
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Use During Plastic Surgery Physical Examinations

Abstract: Background: Medical chaperones often play an important role during physical examinations, providing patient comfort and serving as medicolegal witness. The purpose of this study was to evaluate and compare practices regarding chaperone use by plastic surgery attendings and trainees. Methods: Avoluntary survey was distributed to members of the American Council of Academic Plastic Surgeons. The survey included a standardized set of questions regarding physician demographics, nature of practice training, and curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…These studies comprised 997 medical professionals, 465 patients, and other participants involved in chaperone documentation. Three studies were conducted in the United Kingdom (Molajo et al, 2011(Molajo et al, , 2012Touil et al, 2019) and four studies were conducted in the United States (Choudry et al, 2013;Cuccolo et al, 2019Cuccolo et al, , 2022Vakayil et al, 2019). As shown in Table 2, we considered Plastic and Aesthetic Nursing www.PANjournal.org three studies as low risk of bias (Choudry et al, 2013;Cuccolo et al, 2022;Vakayil et al, 2019) and four studies as high risk of bias (Cuccolo et al, 2019;Molajo et al, 2011Molajo et al, , 2012Touil et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These studies comprised 997 medical professionals, 465 patients, and other participants involved in chaperone documentation. Three studies were conducted in the United Kingdom (Molajo et al, 2011(Molajo et al, , 2012Touil et al, 2019) and four studies were conducted in the United States (Choudry et al, 2013;Cuccolo et al, 2019Cuccolo et al, , 2022Vakayil et al, 2019). As shown in Table 2, we considered Plastic and Aesthetic Nursing www.PANjournal.org three studies as low risk of bias (Choudry et al, 2013;Cuccolo et al, 2022;Vakayil et al, 2019) and four studies as high risk of bias (Cuccolo et al, 2019;Molajo et al, 2011Molajo et al, , 2012Touil et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…According to the American Society of Plastic Surgeons, 92% of all patients undergoing plastic surgery are female, yet the ratio of female to male plastic surgeons is 1:5 24,25 . It is, therefore, recommended that a same-sex chaperone is present during a sensitive examination to ensure the patient's safety and comfort 26 . However, Choudry et al 27 found that only 30% of plastic surgeons reported “always” using chaperones, and the percentage increased to 60% when examining more sensitive areas and a higher rate of male plastic surgeons reported using chaperones.…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Sharma et al 28 reported 68% of patients felt more at ease with the use of a chaperone. Overall, patients preferred to have a same-sex chaperone present, especially during sensitive examinations 26 . Same recommendation should be applied to telemedicine visits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations